GENERAL MODEL AND STABILITY STUDY OF CYLINDIRCAL GRINDING CHATTER (MT) - CHI YuLun; LIU Bin; SHEN YiFeng (Jixie qiangdu)
In order to effectively solve the chatter problem in cylindrical grinding and improve the product quality, a general dynamic model for cylindrical grinding was established based on the regenerative chatter theory. The overlapping factor related to the width of the grinding wheel was introduced into the general dynamic model to fully consider the regenerative chatter relationship between the workpiece and the grinding wheel, and it can be used in longitudinal grinding and circular cutting grinding. In this model, Newton iterative method was used to solve the transcendental equation with time delay, Gaussian elimination method was used to improve the iterative convergence speed, the continuation algorithm was used to continuously provide effective initial values to improve the accuracy of the iterative results, and the accurate grinding stability boundary was obtained. Finally, an experimental research on the grinding and processing of the plunge grinding micro-chatter was conducted. The experimental results show that the universal model can effectively describe the process of cylindrical plunge-cut grinding chatter, and effectively avoids grinding micro vibration lines phenomenon by the model selection of grinding parameters. The model can be effectively used in improving the quality and the efficiency.